B163 Delivering a high-quality regional anaesthesia fellowship during a global pandemic. (11th August 2022) - Haddad, S; Agarwala, R; Pal, A; Cuthbert, S; Bellew, B
Abstract : Background and Aims: COVID-19 has affected the delivery of postgraduate medical education. Social-distancing measures, lost training time and limited resources have all presented unique challenges. Learning opportunities in Regional Anaesthesia (RA) have reduced since the start of the pandemic, yet less aerosol-generation and improved patient flow when compared to general anaesthesia, has increased RA demand. 1, 2 We aimed to combat these challenges by adopting a novel approach to RA fellowship teaching to maintain high-quality training and service delivery. Methods: Fellows were given access to a repository of learning resources through Dropbox™ including research papers and block performance videos. Tutorials were conducted over Microsoft Teams ( Figure 1 ), utilising sono-anatomy videos and immersive anatomy software (3D Organon™) using virtual reality (VR) headsets (Oculus™). Butterfly IQ™ handheld ultrasound devices were made available for practice at home. A Google Docs ™ survey was then distributed to all fellows to rate their learning experience. Results: All fellows (n=6) agreed/strongly agreed that the Dropbox™ folder improved knowledge of RA and aided preparation for online tutorials. All fellows strongly agreed online tutorials were useful. 5 fellows agreed/strongly agreed that VR software was useful for learning, with 3 agreeing/strongly agreeing that the Butterfly IQ™ benefitted their learning. Conclusions: A growing demand for RA, coupled with a greater emphasis on robust training and service delivery, means the provision of high-quality RA fellowships is more important than ever. 3, 4 Despite limitations on medical education during the pandemic our centre has demonstrated it is still possible to maximise RA learning opportunities and keep fellows engaged.